Morphological rearrangements of the rat’s adrenal cortex under conditions of prolonged exposure to heavy metal salts and non-hormonal correction. - Hryntsova, N. B.; Romanіyk A. M.; Bumeister, V. I. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Heavy metal salts adversely affect the health of the population and cause the development of pathology of individual organs and systems of the body. The adrenal glands occupy one of the key places in the regulation and maintenance of the basic functions of the body. Objective. The study of morphological adaptive rearrangements of the structural components of the adrenal cortex of adult mature males under conditions of prolonged exposure to heavy metal salts and non-hormonal correction by vitamin E remains a relevant and under-studied topic. Methods. The experiment was conducted on 24 white mature male rats weighing 200-250 g at the age of 5-6 months, which after a long (90-day) influence of the combination of salts of heavy metals: zinc (ZnSO4 · 7H2O) - 5 mg / l, copper (CuSO4 5H2O) - 1 mg / l, iron (FeSO4) - 10 mg / l, manganese (MnSO4 · 5H2O) - 0.1 mg / l, lead (Pb (NO3) 2) - 0.1 mg / l and chromium (K2Cr2O7) - 0.1 mg / l for 30 days consumed or dinary drinking water with vitamin E correction drug (9.1 mg / kg 10% oil solution). The conventional histological examination methods were applied. Results. The antioxidant L-tocopherol, upon admission to the body of a combination of salts of heavy metals, revealed a reliable stress-protective effect on all the structural components of the adrenal gland: the state of the vascular wall, the nuclear and secretory apparatus spongiocytes of all zones of the cortex. Conclusion. L-tocopherol helps to reduce the toxic effects of heavy metal salts on the adrenal cortex, exerts a membrane-protective and stress-protective effect, attenuates the manifestations of the stage of exhaustion of the general adaptation syndrome, partially restores the hormonal activity of adrenocorticocytes. However, the 30-day period of correction of morphological alterations caused by the entry into the body of heavy metal salts is insufficient for the complete restoration of the state of the vascular wall, the rheological properties of blood and the secretory activity of cells of the adrenal cortex.